Hysteresis in the resistance of a graphene device induced by charge modulation in the substrate - Brant, Juliana Caldeira (2010)
We have fabricated graphene devices on lightly doped Si substrates and show that pronounced changes in resistance versus gate voltage, R Vg , characteristics of these devices at 77 K are induced by the variation in the charge distribution in substrate with both gate voltage and illumination. The R Vg of the graphene devices in the dark shows remarkable changes as the carriers in the underlying substrate go through accumulation, depletion, and inversion regimes. We demonstrate the possibility of using a graphene device as an optical-latch.